Prospective Validation of a Biomarker-Based Rule Out Strategy for Functionally Relevant Coronary Artery Disease. (1st February 2018) - Walter, Joan E; Honegger, Ursina; Puelacher, Christian; Mueller, Deborah; Wagener, Max; Schaerli, Nicolas; Strebel, Ivo; Twerenbold, Raphael; Boeddinghaus, Jasper; Nestelberger, Thomas; Sazgary, Lorraine; Marbot, Stella; et al.
Abstract: BACKGROUND: This study aimed to prospectively advance a rule-out strategy for functionally significant coronary artery disease (CAD) by use of high-sensitivity cardiac troponin I (hs-cTnI) from bench to bedside, by application of a 3-step approach: validation in serum, correlation in plasma, and application on a clinical platform. METHODS: Patients without known CAD referred for rest/stress myocardial perfusion single-photon emission tomography/computer tomography (MPI-SPECT/CT) were assigned to 3 consecutive cohorts: validation, correlation, and application. Functionally relevant CAD was adjudicated with the use of expert interpretation of MPI-SPECT/CT and, if available, coronary angiography. In the validation cohort resting hs-cTnI was measured in serum before stress testing with the research Erenna system, in serum and plasma in the correlation cohort with the research Erenna system, and in plasma in the application cohort with the clinical Clarity system. RESULTS: Overall, functionally relevant CAD was adjudicated in 21% (304/1478) of patients. In the validation cohort (n = 613), hs-cTnI concentrations were significantly higher in patients with functionally relevant CAD (median 2.8 ng/L vs 1.9 ng/L, P < 0.001) as compared to patients without functionally relevant CAD and allowed a rule out with 95% sensitivity in 14% of patients. In the correlation cohort (n = 606), hs-cTnI concentrations in serum and plasma strongly correlated (Spearman r = 0.921) and had similar diagnostic accuracy as quantified by the area under the receiver operating characteristic curve (0.686 vs 0.678, P = 0.425). In the application cohort (n = 555), very low hs-cTnI plasma concentrations (< 0.5 ng/L) ruled out functionally relevant CAD with 95% sensitivity in 10% of patients. CONCLUSIONS: A single resting plasma hs-cTnI measurement can safely rule out functionally relevant CAD in around 10% of patients without known CAD.